The Influence of Web Based Wordwall Audiovisual Media Usage on Learning Motivation in Social Studies Subjects For Grade V Elementary School Students - K, Andi Zulfadilah; Achmad, Widya Karmila Sari; Tati, Andi Dewi Riang (International Journal of Elementary School Teacher, 2024)
This research aims to investigate the implementation of learning using web based Wordwall audiovisual media, examine the description of student learning using web-based Wordwall audiovisual media and determine the influence of web based Wordwall audiovisual media on learning motivation in Social Studies subject in class V UPT SDN 4 Barru. The method used in this research is The Quasi Experimental Design and using a pretest – posttest control group design model. The data collection techniques used questionnaires, observation, and documentation. The data analysis and inferential statistical analysis, consisting of test normality, homogeneity and hypothesis using the Mann-Whitney U test. The Mann Whitney test was carried out because there was one of the data that was not normally distributed and was not homogeneous. The result of the descriptive analysis of the study showed that the learning process using web based Wordwall audiovisual media was very well implemented. The result of the inferential analysis using Mann Whitney showed that the sig (2-tailed) value was 0,024 < 0,05, so the null hypothesis H0 was rejected and H1 was accepted. When using web based Wordwall audiovisual media, students were more enthuaiastic about participacing in learning process. This can be seen from the students who were actively involved in the learning process. So it can be concluded that the learning process using web based Wordwall audiovisual media was very well implemented, student learning motivation in Social Studies subject increased, and there was a significant effect after using web based Wordwall audiovisual media on student learning motivation in Social Studies subject in class V UPTD SDN 4 Barru.